Office safety - Idea Bank (Santa Barbara, Clifornia : Idea Group, New York : Distributed by Insight Media, 1991)
Video covers safe lifting techniques, fire prevention, controlling stress, protecting against repetitive strain injury and reducing eyestrain & workstation glare
Chris Davis, narrator
DVD.
No Master.
Keywords: Office buildings -- Safety measures; Safety; Office practice -- Safety measures; Accidents -- Prevention; Stress management